Legal Protection of Consumers for Cosmetic Products in Container Packaging (Share In Jar) - Khoiroh, Aimmatul; Silado, Audrey Bintang; Valoka, Metta; Saly, Jeane Neltje (CV. Rayyan Dwi Bharata, 2023)
Container packaging (share in jar) is dividing the contents of a product into several small packages. The system in this share in jar is that you have to remove the product to be removed from the original packaging and transferred to another, smaller package. The issues that will be discussed in this journal are how is legal protection for consumers who experience losses as a result of the sale of share in jar cosmetic products and what is the responsibility of business actors for losses experienced by consumers who use share in jar cosmetic products. The purpose of writing this journal is to understand the forms and efforts to protect the law against consumers for the use of cosmetic products with share in jar packaging and to find out the responsibility of business actors for losses suffered by consumers who use cosmetic products with share in jar packaging. The type of research method used in this journal is normative juridical. Based on the journals made by the authors, this journal tells about legal protection for consumers and the responsibility of business actors for losses experienced by consumers who use cosmetic products in the form of container packaging (share in jar).